Commercial advertisements in the Almanak de Piracicaba para 1900: typeface repertoire and typographic composition - Pniewski, Beatriz; Piaia, Jade Samara (InfoDesign, 2023)
Through the analysis of the Almanak de Piracicaba para 1900, printed by the Hennies Brothers Letterpress Printing Shop, this article seeks to understand how commercial advertisements were made at the turn of the nineteenth to the twentieth century. The collection and cataloging of typefaces used in the composition of these ads has assisted in investigating their visual styles and comparing these ads with each other, as well as contributed to the study of the Hennies Brothers Letterpress Printing Shop and São Paulo graphic memory as a whole.